2006
DOI: 10.1074/jbc.m509179200
|View full text |Cite
|
Sign up to set email alerts
|

Tid1 Isoforms Are Mitochondrial DnaJ-like Chaperones with Unique Carboxyl Termini That Determine Cytosolic Fate

Abstract: Tid1 is a human homolog of bacterial DnaJ and the Drosophila tumor suppressor Tid56 that has two alternatively spliced isoforms, Tid1-long and -short (Tid1-L and -S), which differ only at their carboxyl termini. Although Tid1 proteins localize overwhelmingly to mitochondria, published data demonstrate principally nonmitochondrial protein interactions and activities. This study was undertaken to determine whether Tid1 proteins function as mitochondrial DnaJ-like chaperones and to resolve the paradox of how prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
95
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 47 publications
6
95
0
Order By: Relevance
“…It was shown that Tid1-L is much more stable in the cytosol than Tid1-S, while both were equally stable inside the mitochondria (Lu et al 2006). Thus, it was very interesting to examine whether Tid1-S and Tid1-L exhibit different reactivation activities.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was shown that Tid1-L is much more stable in the cytosol than Tid1-S, while both were equally stable inside the mitochondria (Lu et al 2006). Thus, it was very interesting to examine whether Tid1-S and Tid1-L exhibit different reactivation activities.…”
Section: Resultsmentioning
confidence: 99%
“…4. Since a previous study showed that both Tid1-L and Tid1-S are equally able to complement deletion of yeast Mdj1, we initially focused on studying Tid1-L (Lu et al 2006). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations